The evolution of food security in Japan—Based on an indicator evaluation system including climate change indicators - Caixia Li (PLoS ONE, 2025)
As climate change intensifies, food security has received widespread attention. This study examines the development of Japan’s food security index and its relationship with climate change. From these findings, a food security indicator system for Japan was established. The food security system has six dimensions: availability, nutrition, climate change, society, economics, and fertilizer. The factors affecting food security are complex and variable, and this paper adds the Fertilizer Security Index (FSI) to the previous studies. The overuse of fertilizers directly contributes to soil and atmospheric pollution, which can indirectly lead to issues of food quality insecurity. Including this factor within the food security system is fully justified. This enhances the precision of the food security index system to some degree. The results showed that Japan’s overall food security index exhibited a slight downward trend from 0.113 in 1980 to 0.099 in 2022. Food security reached its lowest point of about 0.067 in 1993. In addition, all five indicators, except the fertilizer index, put pressure on the food security index. Due to the uncertainty inherent in climate change, specifically its ambiguous positive and negative impacts on food security, the Climate Change Security Index provides detailed evidence in this paper supporting whether climate change contributes to or undermines food security. Finally, the study put forward recommendations to ensure food security.